Five-Phase Permanent Magnetic Synchronous Motor Fed by Fault Tolerant Five Phase Voltage Source Inverter - Hichem Kesraoui; Hamdi Echeikh; Atif Iqbal; Med Faouzi Mimouni (Institute of Advanced Engineering and Science, 2016)
Multiphase machines have gained attention in numerous fields of pplications such as Aircraft, ship propulsion, petrochemical and automobiles, where high reliability is required. The additional number of phases guarantees that the system continues to operate in faulty conditions compared to the traditional three-phase machine due to the high degree of freedom. Among faults able to affect multiphase system, break between a machine phase and the voltage source inverter (VSI) degrade the performance of the control. In this paper, a five-phase permanent magnet synchronous machine (PMSM) is fed through a fault tolerant voltage source inverter with new structure to ensure drive continuity when open circuit occurs. The five phase PMSM is controlled with fuzzy logic regulator to minimize disturbance impact that can arise fault condition. Paper is accomplished with real time simulations using MATLAB-Simulink in order to validate the new topology and show the effectiveness of the proposed solution.